Perianal and gluteal lipomatosis in a child: A case report - Juan R. Medina-Morell; Kenneth Avilés-Fernández; Zabeth Krystal Hernandez-Sanchez; Victor Ortiz-Justiniano (Elsevier, 2024)
Introduction: Angiolipomatosis is a rare benign condition involving subcutaneous fat and blood vessels, particularly uncommon in pediatric patients. Case presentation: An 11-year-old male presented with multiple firm, non-tender masses in the right gluteal and perianal regions, the largest measuring 8 cm for approximately 8 months duration. The patient underwent staged surgical excisions under general anesthesia due to extensive disease burden. In the first stage, perianal and medial gluteal masses were excised. Lipomatous masses were carefully dissected from the external anal sphincter to the posterior superior iliac spine (PSIS) with preservation of the external anal sphincter. The procedure was well tolerated, but the patient developed a postoperative wound infection, requiring intravenous antibiotics, debridement, and the creation of a loop colostomy to control wound contamination. Six weeks later, a second-stage excision removed the remaining gluteal masses, including a palpable mass measuring 8 x 4 × 2.5 cm. Hemostasis was achieved, and a Jackson-Pratt drain was placed to manage post-op wound fluid accumulation. The patient recovered well after both surgeries and at the 3-month follow-up, there were no complications. Pathological analysis confirmed angiolipomatosis in the gluteal region and diffuse lipomatosis in the perianal region. No recurrence was observed over a 3-year follow-up period. Conclusion: Angiolipomatosis should be considered as a differential diagnosis for pediatric soft tissue masses in uncommon locations like the gluteal and perianal regions. Atypical presentations can be successfully managed with careful surgical planning helping to avoid unnecessary radical procedures. A staged approach is recommended when encountering diffuse disease, as in this case, and consideration should be given to diverting ostomy if wound contamination is a concern.